Atomistic Hartree theory of twisted double bilayer graphene near the magic angle. (1st June 2022) - Cheung, Christopher T S; Goodwin, Zachary A H; Vitale, Valerio; Lischner, Johannes; Mostofi, Arash A
Abstract: Twisted double bilayer graphene (tDBLG) is a moiré material that has recently generated significant interest because of the observation of correlated phases near the magic angle. We carry out atomistic Hartree theory calculations to study the role of electron–electron interactions in the normal state of tDBLG. In contrast to twisted bilayer graphene, we find that such interactions do not result in significant doping-dependent deformations of the electronic band structure of tDBLG. However, interactions play an important role for the electronic structure in the presence of a perpendicular electric field as they screen the external field. Finally, we analyze the contribution of the Hartree potential to the crystal field, i.e. the on-site energy difference between the inner and outer layers. We find that the on-site energy obtained from Hartree theory has the same sign, but a smaller magnitude compared to previous studies in which the on-site energy was determined by fitting tight-binding results to ab initio density-functional theory (DFT) band structures. To understand this quantitative difference, we analyze the ab initio Kohn–Sham potential obtained from DFT and find that a subtle interplay of electron–electron and electron–ion interactions determines the magnitude of the on-site potential.